2014
DOI: 10.1002/ejoc.201301695
|View full text |Cite
|
Sign up to set email alerts
|

1,2,3‐Triazole in Heterocyclic Compounds, Endowed with Biological Activity, through 1,3‐Dipolar Cycloadditions

Abstract: 1,3-Dipolar cycloaddition reactions can be considered a powerful synthetic tool in the building of heterocyclic rings, with applications in different fields. In this review we focus on the synthesis of biologically active compounds possessing the 1,2,3-triazole core through 1,3-dipolar cycloaddition reactions. The 1,2,3-triazole skeleton can be present as a single disubstituted ring, as a linker between two molecules, or embedded in a polyheterocycle. The cycloaddition reactions are usually catalysed by copper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(128 citation statements)
references
References 111 publications
(146 reference statements)
1
124
0
Order By: Relevance
“…While this ruthenium-catalyzed azide alkyne cycloaddition (RuAAC) has as yet not found as prevalent use as the CuAAC reaction, reports of its application are increasing rapidly. Although, the RuAAC reaction has been briefly mentioned in several reviews on triazole formation [13][14][15][16][17][18][19][20][21][22][23] and metalcatalyzed reactions, [24][25][26] by now a comprehensive survey focused solely on RuAAC is needed.…”
Section: Peptide Side-chain Mimeticsmentioning
confidence: 99%
“…While this ruthenium-catalyzed azide alkyne cycloaddition (RuAAC) has as yet not found as prevalent use as the CuAAC reaction, reports of its application are increasing rapidly. Although, the RuAAC reaction has been briefly mentioned in several reviews on triazole formation [13][14][15][16][17][18][19][20][21][22][23] and metalcatalyzed reactions, [24][25][26] by now a comprehensive survey focused solely on RuAAC is needed.…”
Section: Peptide Side-chain Mimeticsmentioning
confidence: 99%
“…This showed that the triazoles linker between rGO and AuNPs were very efficient for charge separation and electron transfer [203]. In the field of biology, click chemistry has also been extensively used with various successful biological, chemical and medicinal applications [204] including nucleic acid ligation [205], bioconjugation for protein modification [206], drug design [207], gel syntheses for biomedical applications [208], chemical modification of biological molecules [209], and biomolecular labeling [210] activity-based protein profiling (ABPP) [211].…”
Section: Applications Of the Cuaac "Click" Reactionsmentioning
confidence: 99%
“…Various heterocycles containing triazole ring . have been synthesized [2][3][4][5][6][7][8][9][10]. They show a variety of interesting biological activities and can be used as antimicrobial agents [2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%